Mothers’ education and the effectiveness of nutrition programmes: Evidence from a matched cross-sectional study in rural Bangladesh - de Hoop, Thomas; Fallon, Shelby; Yunus, Fakir Md; Munrat, Sabeth; Jolly, Saira Parveen; Sehrin, Farzana; Aktar, Bachera; A Ghani, Ruhina Binta; Sennett, Joshua (Taylor & Francis, 2022)
This article was published in The Journal of Development Effectiveness [ © 2020 Rights managed by Taylor & Francis] and the definite version is available at: https://doi.org/10.1080/19439342.2020.1828998. The Journal's website is at: https://www.tandfonline.com/doi/full/10.1080/19439342.2020.1828998